2016
DOI: 10.1002/pssb.201600289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of applied electric fields on optical responses in elliptical quantum nanosystems

Abstract: The optical absorption response of an elliptical quantum‐dot‐type nanostructure is investigated by numerically determining the electron states within the effective mass and parabolic approximations via the finite element method, taking into account the effect of an externally applied electric field. Validation of the numerical procedure is discussed through the comparison with analytical results of previous works for zero external field conditions. For finite field, the comparison is made with the outcome of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…These quasi‐zero‐dimensional nanostructures become suitable for many applications, such as solar cells, lasers, device screens, etc. Specifically, elliptical QDs have been the subject of very recent research . Rezaei et al reported that nonlinear optical properties are strongly dependent on external optical intensity, size, and geometry of the dot.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These quasi‐zero‐dimensional nanostructures become suitable for many applications, such as solar cells, lasers, device screens, etc. Specifically, elliptical QDs have been the subject of very recent research . Rezaei et al reported that nonlinear optical properties are strongly dependent on external optical intensity, size, and geometry of the dot.…”
Section: Introductionmentioning
confidence: 99%
“…Special emphasis was given to the particular features of their optical response as well as to the possibility of tailoring them as functions of the QD size and geometry. These quasi-zerodimensional nanostructures become suitable for many applications, such as solar cells, lasers, device screens, [1][2][3][4][5] etc. Specifically, elliptical QDs have been the subject of very recent research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation